The Role of Stakeholders in Developing Agricultural Educational Tourism Attractions in Tegalsumedang Village, Bandung Regency - Gusdi, Taqiy; D. Dienaputra , Reiza; Rakhman, Cecep Ucu (Barista : Jurnal Kajian Bahasa dan Pariwisata, 2024)
Tegalwisata Village is one of the villages located in Rancaekek District, Bandung Regency, West Java. This village has topographic and demographic potential that can be developed into tourism, with the development of tourism villages, the right stakeholders are needed so that the village can be developed effectively and efficiently. Agricultural educational tourism itself is explained as educational tourism that focuses on business activities in an organization that manages biological assets and sells and converts related things into agricultural products and other biological assets. This research seeks answers to the problem of stakeholder positions in tourism development. The Pentahelix Stakeholder method is used in identifying stakeholders who play a role in village development. This method reviews each role of stakeholders ranging from government, local entrepreneurs, communities, academics, and the media. This research is a qualitative study taken with observation and interview methods. The main result of this research discusses the position of each stakeholder in the development of tourism villages. This research shows that each stakeholder has performed their roles well. However, the roles recorded have not yet led to the tourism sector. The results of the research show that there needs to be direction to the tourism sector for each stakeholder in Tegalsumedang Village. In addition, human resource development and media stakeholder development to meet the needs of the media role in Tegalsumedang Village.